A case of microscopic polyangiitis in an elderly patient presenting predominantly with cholecystitis successfully treated with mizoribine. Issue 6 (November 2014) - Ichinose, Kunihiro; Iwanaga, Nozomi; Okada, Akitomo; Tamai, Mami; Yamasaki, Satoshi; Nakamura, Hideki; Origuchi, Tomoki; Kawakami, Atsushi
Abstract An 82-year-old woman was previously diagnosed with cholecystitis and treated with antibiotics at another hospital. Because her fever and inflammation persisted, therapeutic cholecystectomy was performed. Histopathology of the gallbladder revealed periarterial vasculitis. After transfer to our hospital, an elevated titer of myeloperoxidase–antineutrophil cytoplasmic antibody (MPO–ANCA) was observed (47 U/mL). The patient's renal dysfunction had previously been thought to be sequelae of her cholecystectomy. We diagnosed microscopic polyangiitis (MPA) and began treatment with 40 mg orally of prednisolone daily. The titer of MPO–ANCA decreased with the treatment, but fever recurred with prednisolone taper. We, therefore, added 50 mg orally of mizoribine (MZR) daily as an immunosuppressant and increased the MZR to 100 mg daily while monitoring its blood peak concentration. The peak level of MZR was 1.58 μg/mL at 6 h after administration. After adding MZR, we successfully tapered the orally dosed prednisolone without recurrent fever or complications. We describe this case of MPA in an elderly patient manifesting predominantly with cholecystitis and successfully treated with orally dosed prednisolone and MZR.